2020
DOI: 10.1111/anu.13091
|View full text |Cite
|
Sign up to set email alerts
|

Using stable isotope analysis to assess the relationship among dietary protein sources, growth, nutrient turnover and incorporation in Nile tilapia ( Oreochromis niloticus )

Abstract: Nile tilapia (1.20 g) were fed for 56 days in five treatments (FM100 containing only fish meal [FM] as a protein source; soybean meal (SBM) replace 25%, 50%, 75% and 100% of FM protein in the diets of FM75, FM50, FM25 and FM0, respectively) to assess the effects of dietary protein sources on growth, turnover half‐life of nitrogen and carbon stable isotopes (δ13C and δ15N) in muscle, isotope discrimination factors (Δ15N and Δ13C), and the relative contribution of protein sources to muscle growth. Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…That is, the heavy isotopic forms (for nitrogen and carbon, 13 C and 15 N) are preferentially retained in tissues, while the light isotopic forms ( 12 C, 14 N) are excreted. 6 This metabolic effect leads to isotopic differences between animal consumers and their respective diets (isotopic discrimination factors, IDFs).…”
Section: S Tab Le Isotope Analys Is -Prin Ciple Of Appli C Ati Onmentioning
confidence: 99%
See 4 more Smart Citations
“…That is, the heavy isotopic forms (for nitrogen and carbon, 13 C and 15 N) are preferentially retained in tissues, while the light isotopic forms ( 12 C, 14 N) are excreted. 6 This metabolic effect leads to isotopic differences between animal consumers and their respective diets (isotopic discrimination factors, IDFs).…”
Section: S Tab Le Isotope Analys Is -Prin Ciple Of Appli C Ati Onmentioning
confidence: 99%
“…These isotopic differences can be natural or manipulated. For example, in micro-and macroalgae, it has been shown that the isotopic values of carbon and nitrogen ( 13 C/ 12 C and 15 N/ 14 N, respectively, expressed in delta notation as δ 13 C and δ 15 N, Table 1) can be manipulated by specific culture media (nitrogen) and through the use of supplementary CO 2 (carbon). 8,9 Once a 'desired' isotopic value has been reached, for example, in microalgae, the biomass can be used to modify the isotopic values of zooplankton, and this, in turn, can be fed to larval organisms to trace nutrients and/ or to quantify contributions of dietary items to growth.…”
Section: S Tab Le Isotope Analys Is -Prin Ciple Of Appli C Ati Onmentioning
confidence: 99%
See 3 more Smart Citations